Proving math is broken with Euler's Formula

Algebra Level 3

Derya claims that he proved that i = 0 i=0 using Euler's formula. Which step contains his first mistake?

Step 1: e i x = cos ( x ) + i sin ( x ) Step 2: i x = ln ( cos ( x ) + i sin ( x ) ) Step 3: i = ln ( cos ( x ) + i sin ( x ) ) x Step 4: i = ln ( cos ( 2 π ) + i sin ( 2 π ) ) 2 π Step 5: i = ln ( 1 ) 2 π Step 6: i = 0 2 π Step 7: i = 0 \begin{aligned} \text{Step 1:}&& { e }^{ ix }&=\cos { (x) } +i\sin { (x) } \\\\ \text{Step 2:}&& ix&=\ln { \big(\cos { (x) } +i\sin { (x) } \big) } \\\\ \text{Step 3:}&& i&=\frac { \ln { \big(\cos { (x) } +i\sin { (x) } \big) } }{ x } \\\\ \text{Step 4:}&& i&=\frac { \ln { \big(\cos { (2\pi ) } +i\sin { (2\pi ) } \big) } }{ 2\pi } \\\\ \text{Step 5:}&& i&=\frac { \ln { (1) } }{ 2\pi } \\\\ \text{Step 6:}&& i&=\frac { 0 }{ 2\pi } \\\\ \text{Step 7:}&& i&=0 \end{aligned}

Step 1 Step 2 Step 3 Step 4 Step 5 Step 6 Step 7 None of the steps contain a mistake

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Arjen Vreugdenhil
May 10, 2018

The complex logarithm is multi-valued, since e z = e z + 2 n π i e^z = e^{z + 2n\pi i} for any integer n n . Assuming equality in Step 2 \boxed{\text{Step 2}} is therefore unwarranted.

It is customary to define ln z = a + b i \ln z = a + bi in such a way that π < b π -\pi < b \leq \pi ; with this definition it is true that ln 1 = 0 \ln 1 = 0 . However, by sustituting x = 2 π x = 2\pi , Derya essentially concludes that e 0 = e 2 π i 0 = 2 π i , e^0 = e^{2\pi i} \ \ \ \therefore\ \ \ \ 0 = 2\pi i, which is invalid.


The correct derivation would be:

Step 1: e i x = cos ( x ) + i sin ( x ) Step 2: i x = ln ( cos ( x ) + i sin ( x ) ) + 2 π i k for some integer k Step 3: i = ln ( cos ( x ) + i sin ( x ) ) + 2 π i k x or x = 0 , k = 0 Step 4: i = ln ( cos ( 2 π ) + i sin ( 2 π ) ) + 2 π i k 2 π Step 5: i = ln ( 1 ) + 2 π i k 2 π Step 6: i = 0 + 2 π i k 2 π Step 7: i = i k . \begin{aligned} \text{Step 1:}&& { e }^{ ix }&=\cos { (x) } +i\sin { (x) } \\\\ \text{Step 2:}&& ix&=\ln { \big(\cos { (x) } +i\sin { (x) } \big) } + 2\pi i k \ \ \ \text{for some integer}\ k \\\\ \text{Step 3:}&& i&=\frac { \ln { \big(\cos { (x) } +i\sin { (x) } \big) } + 2\pi i k }{ x }\ \ \ \text{or}\ x = 0, k = 0 \\\\ \text{Step 4:}&& i&=\frac { \ln { \big(\cos { (2\pi ) } +i\sin { (2\pi ) } \big) } + 2\pi i k }{ 2\pi } \\\\ \text{Step 5:}&& i&=\frac { \ln { (1) } + 2\pi i k }{ 2\pi } \\\\ \text{Step 6:}&& i&=\frac { 0 + 2\pi i k }{ 2\pi } \\\\ \text{Step 7:}&& i&=i k. \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...